Endoscopy in Pediatric Eosinophilic Esophagitis - Nguyen, Nathalie; Kramer, Robert E.; Menard-Katcher, Calies (Frontiers in Pediatrics, 2021)
Endoscopy and mucosal biopsies are essential to the diagnosis of EoE by either confirming or excluding mucosal eosinophilia and providing a visual inspection of the esophagus that may be consistent with EoE or suggest other underlying etiologies. Endoscopy also plays an important therapeutic role in the management of EoE including the assessment of treatment response and treatment of associated complications including esophageal stricture and food impaction. Assessment of treatment response largely depends on endoscopy and mucosal biopsies although less invasive strategies may eventually provide alternative means to assess mucosal inflammation. Herein we will review current use of endoscopy in EoE, including recently developed technologies and their role in the management of EoE.